Addressing human mobility in Iberian Neolithic and Chalcolithic ditched enclosures: The case of Perdigões (South Portugal) - Valera, António Carlos (2020)
To access the role of mobility in the social trajectory of Late Neolithic and Chalcolithic societies in the South of Portugal (Southwest Iberia) a project was design to address the human, animal and object/raw material flow present at Perdigões enclosure. Perdigões, located in the inner Alentejo region, has a long chronology from Late Middle Neolithic to Late Chalcolithic/Early Bronze Age (middle 4th and 3rd millennium BC). It is a large complex of ditched enclosures (with at least 16 ditches), presenting several funerary contexts, an abundance of faunal remains and significant concentrations of exogenous materials in tombs. In this study human and animal mobility are addressed through 87Sr/86Sr isotopic analysis. 69 individuals dating from Late Neolithic and Chalcolithic, with provenance from 9 different archaeological contexts inside the enclosures (tombs, ditches and pits) were analysed. Human data are presented along with previously published strontium isotope ratios from fauna (n = 28; Canis familiaris, Bos taurus, Sus sp., Ovis/Capra, Cervus elaphus, Equus sp.) from the same chronological range and several contextual provenances (Zalaite et al., 2018). Plant samples (n = 20) that cover local and peripheral lithologies were used for establishing local bioavailable strontium isotope ranges. To compare with the Perdigões results, 9 human samples from 3 megalithic monuments (Cebolinhos 1, Comenda 1 and Vidigueiras 2) of the local settlement network were also analysed. The results show a significant scaled mobility of humans and animals in Perdigões, a contextual variation between the funerary contexts within the site and a significant contrast with the individuals from local megalithic monuments. These results, combined with other archaeological data at the site, agree with the interpretation of the site as a large aggregation centre integrated in large scale interaction networks.